Utilizing Eco-enzyme for Dormancy Breaking and Germination in Certified Rice Seed Testing - Hendrawati Juliana Sinaga; Diana Sofia Hanfiah; Hamidah Hanum (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Rice is one of the primary food commodities as a staple food in Indonesia. Increasing rice production can be done by using certified seeds. Dormancy is one of the obstacles in the rice seed testing process. Eco-enzyme is expected to be used for breaking dormancy and promoting germination in certified rice seed testing. This study aims to determine the optimal concentration and soaking time of Eco-enzyme in breaking dormancy of Inpari 32 HDB rice seeds and to assess the potential of Eco-enzyme in replacing KNO3 0.2% in breaking dormancy of Inpari 32 HDB rice seeds. This research was conducted in the seed quality testing laboratory of UPTD Food Crop and Horticultural Seed Certification, North Sumatra Province, from September to October 2024. The results of the study showed that the use of eco-enzyme with concentrations of 5%, 10%, and 15% and a soaking period of 24 and 48 hours did not show a significant difference or a significantly increased effect on various germination parameters compared to the use of KNO3.